2014
DOI: 10.1007/s12298-014-0268-9
|View full text |Cite
|
Sign up to set email alerts
|

A maize α-zein promoter drives an endosperm-specific expression of transgene in rice

Abstract: An alpha-zein promoter isolated from maize containing P-box, E motif sequence TGTAAAGT, opaque-2 box and TATA box was studied for its tissuespecific expression in rice. A 1,098 bp promoter region of alpha-zein gene, fused to the upstream of gusA reporter gene was used for transforming rice immature embryos (ASD 16 or IR 64) via the particle bombardmentmediated method. PCR analysis of putative transformants demonstrated the presence of transgenes (the zein promoter, gusA and hpt). Nineteen out of 37 and two out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…We, therefore, used endosperm-specific promoters such as rice glutelin, a popular endosperm-specific promoter and maize α-zein promoter for driving endosperm-specific expression. Earlier, we have demonstrated that the α-zein promoter isolated from maize could drive endosperm-specific expression in transgenic rice (Joshi et al 2015). For genetic transformation studies, we used a tropical inbred UMI29, which was shown to be amenable to genetic transformation in our laboratory (Joshi et al 2014(Joshi et al , 2016.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We, therefore, used endosperm-specific promoters such as rice glutelin, a popular endosperm-specific promoter and maize α-zein promoter for driving endosperm-specific expression. Earlier, we have demonstrated that the α-zein promoter isolated from maize could drive endosperm-specific expression in transgenic rice (Joshi et al 2015). For genetic transformation studies, we used a tropical inbred UMI29, which was shown to be amenable to genetic transformation in our laboratory (Joshi et al 2014(Joshi et al , 2016.…”
Section: Discussionmentioning
confidence: 99%
“…The phosphinothricin resistance gene (bar) was used as the plant selectable marker. Maize zein promoter was isolated earlier in our laboratory (Geetha 2011) and its endosperm-specific expression pattern in the rice model system was demonstrated in our laboratory (Joshi et al 2015). The pZSPPHY construct harbours gusA besides phyA gene ( Fig.…”
Section: Plant Expression Vectormentioning
confidence: 96%
“…The temporal expression pattern of promoters during seed maturation was also inspected by the histological staining of seed longitudinal sections from each transgenic line (Figure 2b). To monitor promoter activity during endosperm development, GUS staining was performed in the seeds of the early broom stage (4-10 DAF), milky stage (14-15 DAF), soft dough stage (17-18 DAF), hard dough stage (20-23 DAF) and mature stage (>28 DAF) (Joshi et al, 2015), and P OsNETE1 -P OsNETE5 -driven GUS expression was not observed in the endosperm. These results indicated that the five promoters are functional and expressed in a nonendosperm tissue-specific manner, although their strength needs further verification.…”
Section: Analysis Of Promoter Activities In Transgenic Ricementioning
confidence: 99%
“…Those promoters responded to several photosystem‐related proteins in the same regions of transgenic switchgrass by fusing with switchgrass MYB4 (Liu et al ., 2018). So far, a number of representative tissue‐ or organ‐specific native promoters have been reported: root‐specific promoters including tomato SIREO and rice RCc3 (Jones et al ., 2008; Xu et al ., 1995), the phloem‐specific promoter of Brassica juncea (Koramutla et al ., 2016), seed‐specific promoters rice glutelin (Wu et al ., 2000), sesame 2S albumin (Bhunia et al ., 2014), corn zein (Joshi et al ., 2015), and bean arcelin (De Jaeger et al ., 2002), and trichome tissue‐specific promoters in mint (Ahkami et al ., 2015; Vining et al ., 2017). A developing xylem (DX) tissue‐specific native promoter was cloned from Pinus densiflora , which was used to enhance plant biomass and produce biofuel precursors (Cho et al ., 2019; Ko et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%